A CASE STUDY: IMPLEMENTATION OF EVIDENCE BASED NURSING: RANGE OF MOTION EXERCISE TO THE PATIENT WITH FRACTURE FEMOR - Windi Oktavia; Mila Karmila; Andika Abdul Malik; Reffi Nantia Khaerunnisa; Ade Fitriani (Genius Journal, 2020)
Introduction: Femur fracture is a break in the continuity or fracture in the thigh caused by external pressure or physical exertion which is characterized by deformities such as shortening of the leg in the fractured part and limitation of motion. Objective: This case study aims to overcome the physical mobility constraints and activity limitations of the patient Method: Physical examination of the fracture of the femur was performed using the head-to-toe method in postoperative patients with Open Reduction Internal Fixation. The North American Nursing Diagnosis Association is used to determine nursing diagnoses. Meanwhile, nursing intervention refers to the Nursing Intervention Classification and the Nursing Outcomes Classification. Result: A nursing diagnosis of physical mobility impairment with the diagnosis number 00085 was given a nursing intervention in the form of a ROM excercise. After 7 days of nursing intervention, physical mobility impairments were resolved with the criteria that the patient's joint movement increased from stiffness to being able to move, the patient's muscle movement increased with muscle strength from 3 to 5, the patient's balance from very disturbed to slightly disturbed, the patient's way of walking from very annoyed to be quite annoyed. Conclusion: ROM Excercise can increase physical mobility aided by using a mobilization aid (crutch), so it is important to do in patients with a diagnosis of impaired physical mobility